Analysis of the Influence of Atmospheric Precipitation on the Spring Level in Jinan. Issue 1 (June 2020) - Lan, Xiaoxun; Xing, Liting; Dong, Yanan; Yao, Chunmei; Cao, Qianqian
Abstract: In order to realize the rational use of groundwater in Jinan and guarantee the continuous gushing of spring water, a hydrogeological survey was conducted in the study area to collect precipitation and spring water level data over the years, and to analyze the correlation between precipitation and spring water level at different time scales and spaces. Research shows that the correlation coefficient between precipitation and spring water level is the largest in the 1960s, and human activities have less influence on spring water, with the increase of groundwater demand from social development and the implementation of related spring protection measures such as groundwater limitation and replenishment, the correlation coefficient between precipitation and spring water level decreased first and then increased, mining volume remains the main factor affecting groundwater levels; precipitation lag time of Xing long Station, Donghong miao Station and Yanzi shan Station is short. The areas where these rainfall stations are located may be suitable for recharge and replenishment. The research results provide technical basis for spring water protection.